The teaching of mathematics in education of youth and adults in a public school of Altamira (PA) (Research, Society and Development, 2020)
This article is the result of a research that had as its general objective to analyze how the methodologies in mathematics teaching reflect on the teaching and learning process of the students of EJA. The place chosen for the research was a public school located in the city of Altamira (PA). Initially we conducted a bibliographic research and, later, a field research, with a questionnaire applied to two teachers who teach Mathematics, where the data were analyzed from a qualitative perspective. It is noticed that the teaching of mathematics in the EJA needs reformulations of the most diverse, starting with the didactic material and the qualification of the teachers, so that there are different methodologies for the teaching of mathematics directed to this public.